2011
DOI: 10.1093/carcin/bgr250
|View full text |Cite
|
Sign up to set email alerts
|

Functional FEN1 genetic variants contribute to risk of hepatocellular carcinoma, esophageal cancer, gastric cancer and colorectal cancer

Abstract: As a DNA repair protein, Flap endonuclease 1 (FEN1) plays crucial parts in preventing carcinogenesis. Two functional germ line variants (-69G > A and 4150G > T) in the FEN1 gene have been associated with DNA damage levels in coke oven workers and lung cancer risk in general populations. However, the role of these genetic variants on gastrointestinal cancer susceptibility is unknown. Therefore, we evaluated the association between these polymorphisms and gastrointestinal cancer risk in two independent case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 13 publications
4
86
0
Order By: Relevance
“…The present study indicated that functional rs174538 and rs4246215 were significantly associated with an increased risk of cancer. These results are consistent to the findings in breast cancer, lung cancer, hepatocellular carcinoma, esophageal cancer, gastric cancer, colorectal cancer and glioma from different medical centers of China (18,(20)(21)(22), which confirmed our speculation that the functional genetic variants in the FEN1 gene may affect cancer risk as common factors.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The present study indicated that functional rs174538 and rs4246215 were significantly associated with an increased risk of cancer. These results are consistent to the findings in breast cancer, lung cancer, hepatocellular carcinoma, esophageal cancer, gastric cancer, colorectal cancer and glioma from different medical centers of China (18,(20)(21)(22), which confirmed our speculation that the functional genetic variants in the FEN1 gene may affect cancer risk as common factors.…”
supporting
confidence: 92%
“…Four studies were review comments. Finally, 13 sub-studies from 4 studies on rs174538 and rs4246215 genotypes and cancer risk were identified (18,(20)(21)(22), including a total of 5,108 cancer cases and 6,382 case-free controls. The characteristics of the included studies are listed in Table I.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…In the current study, we have found the three metforminassociated metabolites significantly associated with two genes, FEN1 and C20orf94, which are involved in DNA repair (39,40). This may partly explain that metformin has been shown to influence the prevalence of different types of carcinoma, such as gastrointestinal cancers (39) and leukemia (40).…”
Section: Discussionsupporting
confidence: 48%
“…Beyond its common antihyperglycemic action and its effect in lowering LDL-C, metformin can potentially reduce the risk of cancer mortality and diminish the progression of cancer (38). In the current study, we have found the three metforminassociated metabolites significantly associated with two genes, FEN1 and C20orf94, which are involved in DNA repair (39,40). This may partly explain that metformin has been shown to influence the prevalence of different types of carcinoma, such as gastrointestinal cancers (39) and leukemia (40).…”
Section: Discussionmentioning
confidence: 48%
“…Part of the case-control set has been reported previously. 29 (ii) Beijing set (validation set 1): 250 ESCC patients from the Second Artillery General Hospital PLA (Beijing, China) and sexÀ and age-matched 2 Hospital. Controls were cancer-free individuals selected from a community cancer-screening program (3000 individuals) for early detection of cancer conducted in Huaian city during the same period as the patients were collected.…”
Section: Study Case-control Setsmentioning
confidence: 99%